Use of Pregabalin – A Nationwide Pharmacoepidemiological Drug Utilization Study with Focus on Abuse Potential - Schjerning, O.; Pottegård, A.; Damkier, P.; Rosenzweig, M.; Nielsen, J. (Pharmacopsychiatry, 2016)
Introduction: Pregabalin is currently approved for the treatment of epilepsy, generalized anxiety disorder and neuropathic pain with a licensed dosage range of 150 mg to 600 mg/day. Growing concern about the abuse potential of pregabalin is partly based on reports of pregabalin being used in dosages that exceed the approved therapeutic range.Methods: To identify predictors of pregabalin use above recommended dosage, we conducted a pharmacoepidemological drug utilization study using the Danish nationwide registers. We deployed 4 measures of abuse: high use (≥600 mg/day) or very high use (≥1 200 mg/day) over a 6- or 12-month period, respectively. Multiple logistic regression was used to identify patient and treatment characteristics that were associated with either abuse marker.Results: Out of 42 520 pregabalin users 4 090 (9.6%) were treated with more than 600 mg/day for 6 months and 2 765 (6.5%) for more than 12 months. Male gender and prescription of antipsychotics and benzodiazepines were associated with increased risk of use of above the recommended dosage.Discussion: Use of pregabalin above recommended dosages was rare but abuse may occur in susceptible patients.
Keywords: pregabalin; abuse; drug utilization; denmark